Patterns of Human Capital Formation - Hrydziushka, Aliaksandr; Hrybau, Andrei; Kulakou, Vasili (Olsztyn Economic Journal, 2021)
The main goal of the article is to identify the basic patterns of the formation of human capital (HC). An especially valuable and scarce resource of the modern economy is becoming a creative skilled worker capable of generating ideas, as well as creating and implementing new technological solutions and products. The development of the economy leads to significant transformations in the generation of resource potential, and changes in the role of individual resources. Human capital begins to play a dominant role in the resource hierarchy. It is the HC that sets in motion the production processes and determines the efficiency of using the entire resource potential. The methods of aspect analysis and of apperception used in this study made it possible to identify modern patterns peculiar to the formation of human capital in the economy, and to emphasize its objective importance and ability to significantly influence the development of society. During the research, the authors proved that human capital acquires the status of the main resource in the economy, the quantitative characteristics of the workforce capacity give way to the role of qualitative characteristics, and the development of STP requires a new employee formation to dominate the intellectual component.